2010
DOI: 10.2495/air100241
|View full text |Cite
|
Sign up to set email alerts
|

Indoor air quality assessment in a school building in Chennai City, India

Abstract: During recent years, concerns over the effects of poor indoor air quality (IAQ) have been increased and wide spectrums of symptoms/illnesses are related to indoor air pollution in many urban centers of the world. In India, it is estimated that about half a million women and children die per year due to indoor air pollution. Therefore, maintaining an acceptable IAQ is important in places such as schools, corporate office buildings, hospitals and houses. It is hypothesized that the higher indoor pollutant concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…The negative relationship between temperature and CO and CO2 concentrations shows a tendency for a relationship between reduced CO and CO2 concentrations with rising air temperatures in space. This is in line with research conducted by Talarosha [12] and Nagendra & Harika [13]. In addition, there was a low/weak positive relationship between CO concentration values and CO2 concentration values (0.161 ≥ r ≥0.280) in measurements in three schools.…”
Section: Relationship Between Meteorological Parameter Variables and supporting
confidence: 91%
“…The negative relationship between temperature and CO and CO2 concentrations shows a tendency for a relationship between reduced CO and CO2 concentrations with rising air temperatures in space. This is in line with research conducted by Talarosha [12] and Nagendra & Harika [13]. In addition, there was a low/weak positive relationship between CO concentration values and CO2 concentration values (0.161 ≥ r ≥0.280) in measurements in three schools.…”
Section: Relationship Between Meteorological Parameter Variables and supporting
confidence: 91%
“…Figures 1, 2, and 3 illustrate the analysis, which revealed that around 73% of respondents were happy with the thermal level in the classroom, 65% in the staff room, and 63% in the drawing hall. Therefore, it must take the required steps to increase thermal comfort pleasure throughout, especially in the drawing hall in the summer (Nagendra & Harika, 2010).…”
Section: Results and Findings Results Of Subjective Measurements Surv...mentioning
confidence: 99%
“…Installing HVAC systems and issues within (ducts, filters, maintenance, noise) -Risk of health problems, particularly for airways, skin, and eyes [30] -Increasing indoor moisture and leads to a higher level of microbial growth and dust mites [94][95][96][97][98] The HVAC system causes an inflow of outdoor pollutants [86] Building envelope Air-tighter and more thermally insulated [12] and inadequate air exchange -Diseases include asthma, cold and flu, lung cancer and cardiovascular diseases especially ischemic heart disease [86,99,100]…”
Section: Mechanical Hvac Systemmentioning
confidence: 99%